A comparison of Intravenous Iron versus Oral Iron for the Management of Iron Deficiency Anemia: A Changing Paradigm - Khan, Afaq Ahmad; Wani, Zeeshan Ahmad; Mir, Muzzafer M; Mir, Aadil Ahmad; Kochak, Tufeel Jan; Rathod, Santosh Govind (International Journal of Health and Clinical Research, 2021)
Background: Iron deficiency is one of the major morbidities worldwide. The standard treatment is the oral iron therapy, however, the concerns of slower response makes it a less feasible option in situations where quicker response is desired. The objective of this study was to compare the response, the quickness of the response and tolerability of intravenous iron with that of oral iron. A prospective, observational cohort study was conducted on 300 patients of iron deficiency anemia in District Hospital Srinagar wherein 110 patients received oral iron and 190 patients received intravenous iron. The mean hemoglobin increase at 3 weeks in oral iron group was 1.71 g/dl and in intravenous group it was 2.75 g/dl. Conclusion: Intravenous iron therapy is more effective than oral iron in terms of rapidity of the response.